2021
DOI: 10.7860/jcdr/2021/50742.15560
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Study on Empathy and Factors Associated with Individual Variations in Empathy Levels among College Students in Central Kerala

Abstract: Introduction: Empathy is a social skill that exerts influence on the quality of social relationships. An empathetic person is able to understand the emotions of others, accurately express their feelings, comprehend other’s situations and act appropriately. Added to the volatile nature of the age, the youth face challenges from social exclusion, gender based violence and the lack of access to rights and opportunities. Aim: To measure empathy levels among college students aged 18-28 years in Kerala and to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The author concluded that a good prevalence of empathy and humanistic values are found among college students in Kerala. 11 A study conducted by Prasanna Guru. E, Gheena.S in 2016 January, Chennai to examine the empathy among students from 4 health disciplines among 1 st years and final years.…”
Section: Discussionmentioning
confidence: 99%
“…The author concluded that a good prevalence of empathy and humanistic values are found among college students in Kerala. 11 A study conducted by Prasanna Guru. E, Gheena.S in 2016 January, Chennai to examine the empathy among students from 4 health disciplines among 1 st years and final years.…”
Section: Discussionmentioning
confidence: 99%